Efficacy of social self-value package to improve empowerment and quality of life among people living with HIV under antiretroviral treatment in Nepal : A Randomized controlled trial - Bhatta, Dharma Nand (Prince of Songkla University, 2018)
Thesis (Ph.D.,(Epidemiology (International Program)))--Prince of Songkla University, 2016